(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
This scientific article shows developments in the field of transport in the Republic of Uzbekistan after World War II and their impact on the socio-economic life of the Republic of Uzbekistan, as well as the construction of smooth roads and the growth of freight and passenger traffic in the Republic of Uzbekistan. This article reveals the growth of freight and passenger traffic on the basis of tables.